Human anthrax in Turkey: A ten years' experience (2009–2018). (January 2021) - Topluoglu, Seher; Aktas, Dilber; Celebi, Bekir; Kara, Fatih; Doganay, Mehmet; Alp, Emine
Anthrax is a notifiable disease in Turkey. In order to control the human disease, animal foci are being monitored and prevention and control activities are being implemented by the Ministry of Health in coordination with the Ministry of Agriculture and Forestry. The objective of our study was to evaluate the national surveillance data and control activities in the last decade. A total of 1174 anthrax cases and 9 deaths have been reported. Anthrax was frequent in eastern provinces and in big cities where large animal movements were significant. The incidence rate was 1.5 times higher in males than in females. The disease was more common in the 30–64 age group. The number of cases increased in the summer and autumn seasons. Human anthrax is still being reported though in decreasing numbers in Turkey. A collaborative control programme continues to be needed.